2019
DOI: 10.3390/jcm8111839
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Clinical and Laboratory Parameters Associated with the Development of Acute Chest Syndrome during Vaso-Occlusive Episodes in Children with Sickle Cell Disease: A Preliminary Step before Assessing Specific and Early Treatment Strategies

Abstract: This prospective observational study sought to ascertain clinical and laboratory parameters associated with the development of acute chest syndrome (ACS) during vaso-occlusive episodes (VOE) in children with sickle cell disease (SCD). It was performed at the pediatric department of the university Intercommunal Créteil hospital. All children with SCD (all sickle genotypes) consecutively admitted from November 2013 to December 2016 for painful VOEs and no evidence of ACS were included. Clinical and laboratory pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
11
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(33 citation statements)
references
References 35 publications
19
11
3
Order By: Relevance
“…This differed from the ndings of Madhi et al's observational study, potentially due to dissimilar age groupings between the two. [15] However, our observations aligned with a large multicenter study by Vichinsky et al reporting median ages at rst ACS episode of 5.4-14.6 years in age groups of 0-9 years and 10-19 years, respectively. [7] Notably, our study suggests gender does not in uence post-admission ACS risk on its own within our population.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This differed from the ndings of Madhi et al's observational study, potentially due to dissimilar age groupings between the two. [15] However, our observations aligned with a large multicenter study by Vichinsky et al reporting median ages at rst ACS episode of 5.4-14.6 years in age groups of 0-9 years and 10-19 years, respectively. [7] Notably, our study suggests gender does not in uence post-admission ACS risk on its own within our population.…”
Section: Discussionsupporting
confidence: 92%
“…[2,17,18] It is well established that vaso-occlusive crises (VOCs) are the commonest reason of hospitalization among SCA patients. [1,2,11,17,18] Previous research has shown that following admission for a VOC, approximately 13-20% of patients will go on to develop ACS in initial 3 days over an indolent clinical course.. [11,12,15,19] The aim of our study was to identify risk factors that could predict the development of ACS among pediatric patients with SCA. This will help clinicians focus monitoring and care efforts on higher-risk patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…When considering final diagnosis, over 80% of the cohort had either a VOC or ACS. Madhi et al 17 . have identified pain score, pain location and neutrophil count as independently associated with ACS.…”
Section: Discussionmentioning
confidence: 99%
“…When considering final diagnosis, over 80% of the cohort had either a VOC or ACS. Madhi et al 17 have identified pain score, pain location and neutrophil count as independently associated with ACS. Given that the majority of abnormal CXRs revealed new infiltrates, such parameters incorporated into a clinical score could be used to identify those at risk of ACS, hence determining who would benefit from a diagnostic CXR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation